Control and autonomy of online audiences: Control y autonomía del público en línea - Gallego Torres, Rómulo And´res (Noria Investigación Educativa, 2019)
Based on technological advances and changes in the way people communicate, the task of controlling audiences has become difficult, as these prosumers consume and produce content autonomously, resulting in networking fans who through transmedia narratives disseminate content that brands take advantage of to create community; and from these communities, consumption becomes a networked practice. This brief discusses how, based on emotional marketing, and the use of content marketing the task of building these communities is more efficient.